2011
DOI: 10.1111/j.1600-0854.2011.01205.x
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of the Dileucine‐Based Sorting Motif in HIV‐1 Nef Revealed by Intermolecular Domain Assembly

Abstract: The human immunodeficiency virus 1 (HIV-1) Nef protein is a pathogenicity factor required for effective progression to AIDS, which modulates host cell signaling pathways and T-cell receptor internalization. We have determined the crystal structure of Nef, allele SF2, in complex with an engineered SH3 domain of human Hck showing unnaturally tight binding and inhibitory potential toward Nef. This complex provides the most complete Nef structure described today, and explains the structural basis of the high affin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 59 publications
6
40
0
Order By: Relevance
“…Note that SH3-HART Phe97 (F97; green spheres) occupies the position of I96 in the wild-type crystal structure. Recent crystallographic analysis of a related high affinity Nef-SH3 interface supports this model [29]. …”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Note that SH3-HART Phe97 (F97; green spheres) occupies the position of I96 in the wild-type crystal structure. Recent crystallographic analysis of a related high affinity Nef-SH3 interface supports this model [29]. …”
Section: Resultsmentioning
confidence: 90%
“…Because NaPP1 binds to the Hck-TA active site in a specific location, it serves as a chemical probe for conformational changes that may occur in response to Nef binding. In addition to the gatekeeper mutation, we modified the SH3 domain to enhance interaction with Nef [29,30]. This modification enabled stable association of Hck with Nef in solution-based kinase assays, thus mimicking the stable association that is likely to occur between Hck and Nef at cellular membranes [17].…”
Section: Introductionmentioning
confidence: 99%
“…A precedent for intercomplex Nef⅐SH3 contacts comes from the work of Horenkamp et al (38), in which the x-ray crystal structure of the Nef core domain was determined in complex with an engineered high affinity Hck SH3 domain. This structure, referred to as Nef⅐Hck SH3 B6 , also crystallized as a dimer of complexes with the Nef C-terminal loop making contacts with a hydrophobic crevice adjacent to the SH3 RT-loop recognition site.…”
Section: Resultsmentioning
confidence: 99%
“…We found that residues I123 and L146 are located on two central α helices, which are located within the core domain of Nef (Figure 6A). These two helices are kept in place by the two gatekeeper residues F122 and Y145 (F94 and W117 in HIV- 1 Nef), which divide the intermediate groove into a recognition site for SH3 domains and a binding site for endocytic sorting motifs (Horenkamp et al, 2011). I123 and L146 oppose each other on these two helices at a minimal distance of 4.2 Å but are not directly surface accessible (Figures 6B and 6C).…”
Section: Resultsmentioning
confidence: 99%